Prevalence of misconception about HIV/AIDS transmission and associated factors among reproductive age women in Ethiopia: a nationwide study - Ali Yimer; Abdul-Aziz Kebede Kassaw; Sebwedin Surur; Endris Mussa (BMC Infectious Diseases, 2024)
Abstract Background Misconceptions and myths are still the bottlenecks for the prevention of HIV/AIDS transmission in developing countries. This study aimed to assess the prevalence and associated factors of misconception about HIV transmission among reproductive age groups using the most recently available Ethiopian Demographic and Health Surveydata. Methods A cross-sectional study design was done using the Ethiopian Demographic and Health Survey 2016 data set. The data analysis was conducted using  Statistical Package for Social Sciences version 25. Multivariable logistic regression analysis was done to identify associated factors of misconception about HIV/AIDS transmission. A p-value of < 0.05 and an adjusted odds ratio with a 95% confidence interval were considered to confirm a statistically significant association. Results From the sample of 11,425 reproductive-age women, the prevalence of misconception about HIV/AIDS transmission among reproductive-age women in Ethiopia was 27.47%. Women residing in rural area [AOR:1.24; 95% CI: 1.03–1.75] compared to urban resident participants, attended primary education [AOR:0.58;95%CI: 0.49–0.68], attended secondary education [AOR:0.36;95%CI:0.29–0.46], attended higher education [AOR:0.24;95%CI: 0.18–0.32] compared to those participants without education, had history of HIV test [AOR:0.77; 95%CI: 0.67–0.88] compared to their counterpart, respondents living in Amhara region [AOR:0.44:95% CI:0.35–0.54], Benishangul [AOR: 0.34; 95% CI: 0.25–0.46], SNNPR [AOR:0.50; 95% CI: 0.38–0.67], Gambela [AOR:0.57; 95% CI: 0.42–0.79], Harari [AOR:0.62; 95% CI: 0.46–0.82], Addis Ababa [AOR:0.63; 95% CI: 0.49–0.81] compared to those living in Tigray and having richest wealth status[AOR:0.57;95% CI: 1.457–4.078] compared to those whose wealth index was poorest were significantly associated with the misconception about HIV transmission. Conclusion Over all the prevalence of misconception about HIV/AIDS transmission among reproductive-age women in Ethiopia was high. Residence, educational level, wealth index, region, and respondents who ever tested for HIV were significantly associated with the misconception about HIV/AIDS transmission. This high misconception could affect HIV/AIDS transmission and its prevention strategies unless timely and appropriate intervention should be taken. Strengthening strategies aimed at maximizing HIV/AIDS testing, scaling up educational status, and emphasizing regional-wide interventions might have a substantial contribution.